Sustainable Tourism sebagai Instrumen Strategis dalam Perencanaan Pembangunan Suatu Analisis dari Sisi Pengembangan Destinasi Pariwisata Berkelanjutan - Oka A.Yoeti; I Made Adhi Gunadi (Journal of Tourism Destination and Attraction, 2013)
Sustainable tourism development guidelines and management practices are applicable to all forms of tourism in all types of destinations, and all types of tourism, whether it is ‘mass tourism’ or ‘niche tourism’. Sustainable ways of managing destinations can be defined by considering their competitive position and their stage in the destination life cycle in the interest of achieving sustainable tourism outcomes. This paper discusses factors that could ensure the sustainability of tourism and appropriate policy that needed to be implemented in order to prevent tourism from creating negative environmental and socio-cultural impacts in the respective tourist destinations. Within the discussion, reference is made to several tourism destinations. Towards the end of the paper, planning approaches that are needed to conserve the intrinsic qualities of selected tourism destination are suggested.